2015
DOI: 10.5137/1019-5149.jtn.14094-15.1
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of late term surgical treatment of penetrating peripheral nerve injuries

Abstract: In previous studies, the incidence of PNI has been reported to be 13 to 23 per 100 000 individuals per year. PNIs have been estimated to affect between 1.64% and 2.8% of all trauma patients (24,31). PNI is a common problem, especially in young adult men, and may cause serious disability in this productive age group unless the injured nerve is repaired (1, 22, 24). █ INTRODUCTIONPeripheral nerve injury (PNI) is still a significant cause of morbidity and disability throughout the world. Physical trauma, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Erakat et al [8] reported that the injury to surgery interval is the most significant prognostic factor in a study evaluating the timing of repair of the lingual nerve injury. Gezercan et al [3] reported in a series consisting of 25 nerve injuries repaired 3-30 months after the injury that only 23.4% of the cases had 4-5/5 motor strength at the end of a 15 month follow-up period. There are some studies reporting better clinical results with early primary repair than delayed repair for upper extremity nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erakat et al [8] reported that the injury to surgery interval is the most significant prognostic factor in a study evaluating the timing of repair of the lingual nerve injury. Gezercan et al [3] reported in a series consisting of 25 nerve injuries repaired 3-30 months after the injury that only 23.4% of the cases had 4-5/5 motor strength at the end of a 15 month follow-up period. There are some studies reporting better clinical results with early primary repair than delayed repair for upper extremity nerves.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed to evaluate the effects of immediate versus subacute, or with the term frequently used in literature, delayed primary (after seven days) repair of peripheral nerve injury [3] on histological results of axon degeneration and weights of end-organ muscles in a transaction type sciatic nerve injury model in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The most common approach to repair peripheral nerve injuries is surgical direct repair/direct coaptation 11 . When the gap in a peripheral injury exceeds 5 mm, autograft reconstruction is often used as the "gold standard" treatment 12,13 .…”
Section: Why We Use Biomaterials For Sci Repairmentioning
confidence: 99%